Authentic Leadership (HBR Emotional Intelligence Series). - Review, Harvard Business. (HBR emotional intelligence series., 2017)
Organizations require certain qualities and behaviors from their employees, so much so that many individuals feel they lose who they truly are. Leaders, especially, can struggle to be seen as authority figures when they feel uncertain or emotional. Can you ever really be yourself at work? This book shows you how to balance vulnerability, emotion, and authority, so that you can feel effective at work while also being true to yourself. You'll learn from the latest research who is most at risk for feeling inauthentic, what that means for engagement and credibility, and how to decide when is appropriate to just be yourself--or adapt to your company's culture and expectations.--